Duration of gargling and rinsing among frequent mouthwash users: a cross-sectional study - Eric P F Chow; Jane S Hocking; Catriona Bradshaw; Christopher Fairley; Kate Maddaford; Rebecca Wigan; Sabrina Trumpour; Tiffany Renee Phillips (BMJ Open)
Objective To examine the rinsing and gargling mouthwash practices among frequent mouthwash users to determine if there are differences in use between gender, sexual orientation and sex work status.Design Cross-sectional study.Setting Data obtained from patients attending a sexual health centre located in Melbourne, Australia.Participants 200 frequent mouthwash users (four or more times per week), 50 for each of the following patient groups: men who have sex with men (MSM), female sex workers (FSW), females who are not sex workers and men who have sex with women only (MSW). Participants were observed and audio recorded using mouthwash.Primary and secondary outcome measures Descriptive analyses were conducted to calculate the median age, time rinsing and gargling, amount of mouthwash used and proportion of participants who rinsed, gargled or both, as determined from the audio files. Kruskal-Wallis H test and χ2 test were used to examine differences between the patient groups.Results Median age was 28 years (IQR: 24–33). During the study, most (n=127; 63.5%) rinsed and gargled, but 70 (35.0%) rinsed only and three (1.5%) gargled only. Median time rinsing was 13.5 s (IQR: 8.5–22.0 s), gargling was 4.0 s (IQR: 2.5–6.0 s) and the median total duration was 17.0 s (IQR: 11.5–25.8 s). Median duration of mouthwash did not differ significantly between the groups (females not sex workers: 18.8 s (IQR: 12.5–24.5 s); FSW: 14.0 s (9.0–22.0 s); MSM: 22.3 s (13.0–26.5 s); MSW: 15.8 s (12.0–25.0 s); p=0.070) but males used mouthwash longer than females (median 20.3 s compared with 15.5 s; p=0.034). The median volume of mouthwash used was 20 mL (IQR: 15–27 mL). And most (n=198; 99.0%) did not dilute mouthwash with water.Conclusion Over a quarter of frequent users do not gargle mouthwash at all (35%) and used it for a substantially shorter period of time than it was used in the randomised trial (1 min) where it was shown to be effective at inhibiting Neisseria gonorrhoeae growth. Our findings suggest that many frequent mouthwash users do not follow the manufacturer instructions for using mouthwash and may not use mouthwash in a way that was shown to reduce the growth of oropharyngeal gonorrhoea.